Are Nursing Students’ Early Course and Perceived Performance Related to Their Final and Actual Course Performance? - Oducado, Ryan Michael F (Nurse Media Journal of Nursing, 2019)
Background: Assessing the academic performance of students is imperative for nursing educators. While it is commonly accepted that performance in quizzes is linked with final examination performance, little published empirical data is available among nursing student samples.Purpose: The purpose of this study was to determine the relationship between performance in regular short lecture quizzes and long quiz on the final examination performance of nursing students in a nursing course. Likewise, this study ascertained whether there is a significant relationship between perceived performance and actual performance in the final examination of the course.Methods: A descriptive-correlational study design was used. All 138 second-year nursing students enrolled in the Community Health Nursing course were included in this study. Grades in short quizzes, long test, and final examination were analyzed, and a one item global scale was utilized to determine students’ perceived performance in the final examination. Pearson’s r was employed to determine the relationship between variables.Results: Results revealed that performance in regular short lecture quizzes (p=0.000) and long quiz (p=0.000) were significantly correlated with final examination performance. Moreover, there was a significant relationship between perceived performance and actual performance in the final examination (p=0.000).Conclusion: This study suggests that early performance in the lecture course can significantly influence students’ performance in the final assessment of the course. Nurse educators are encouraged to be proactive in identifying students who are at risk of performing poorly early in the course so that prompt remediation and guidance may be provided to students who are not performing well.